Particle deposition in airway bifurcations in different breathing conditions - Miguel, A. F. (2012)
In this paper, particle deposition in a rigid double bifurcation airway is studied experimentally. The effect of particle size and breathing conditions in the deposition are analyzed. Besides, the effect of airway obstruction (local reduction of airway diameter) that can be originated by some respiratory disorders is also studied. The experiments were performed in conditions of humidity near saturation in order to account for the conditions occurring in the respiratory tree.